Implementasi Media Pembelajaran Audio Visual Dalam Meningkatkan Pemahaman Belajar Al Quran Hadis - Ahmad Darlis; Muhammad Khalidin (Fakultas Syariah IAIN Laa Roiba Bogor, 2019)
The Implementation of Audio Visual Learning Media in Improving Learning Understanding of Al Quran Hadith in Class VII MTs Students. Private Tarbiyah Waladiyah Pulau Banyak. The problems found in the research location were: 1). The learning and teaching process in madrassas, teachers in the field of study of Al-qur'an hadith have not involved students directly with the digital Al-qur'an application from the subject matter of the Al-qur'an hadith study area taught so that students have not been trained in solving various field problems study of Al-qur'an hadith. 2). The unavailability of media that supports learning and teaching activities of Al-quran Hadith in madrasas. The focus of this research is that the researcher focuses on the application of Audio Visual Media and the efforts made by the teacher in the Al-quran Hadith study field to improve students' reasoning abilities. 1). The influence of digital Al-quran-based Audio Visual Media on students' reasoning abilities in the concept of understanding and memorizing Al-quran verses by students of the Tarbiyah Waladiyah Island Many Private Tsanawiyah Madrasah is significant, namely the application of the model helps students to better understand the subject matter. 2). Improved reasoning skills of students on indicators of creative thinking, flexible thinking, original thinking, and detailed thinking after the application of Audio Visual Media to students of Tarbiyah Waladiyah Island Banyak Madrasah Tsanawiyah. 3). Student activities when applied to Audio Visual Media in the Al-quran hadith study at Madrasah Tsanawiyah Tarbiyah Waladiyah Pulau Banyak, students responded well. Keywords: Media; Audio Visual; Comprehension.